Gegar Budaya Ditinjau dari Dukungan Sosial pada Mahasiswa Thailand Selatan (Patani) - Irfani Rizal; Icha Herawati (Journal An-Nafs: Kajian Penelitian Psikologi, 2020)
Cultural differences experienced by Thailand Selatan (Patani) students with Indonesian culture can cause cultural shock to Patani students. Culture shock is a reaction of individual discomfort when entering a new environment. One of the strategies in reducing culture shock is to get social support. This research examines whether there is a correlation between social support and culture shock in Patani students at the Islamic University of Riau. The research method used is quantitative research. Data collection was carried out using a scale of culture shock and social support scale. Pearson product-moment analysis was used to test the proposed hypothesis. Participants numbered 52 people using saturated sample techniques. The results showed that a negative and significant relationship between social support and culture shock in Patani students at the Islamic University of Riau with the r = -0,276 with p 0,024 (p< 0,05). The conclusion from this study shows that the higher the social support, the lower the culture shock. The culture shock was predicted by social support of 7.6%.